ANALISIS CAMPUR KODE ANTAR SESAMA PESERTA KAJIAN KITAB RIYAADUSH SHOLIHIIN DI MASJID NURUL IMAN, BLOK M SQUARE, JAKARTA SELATAN - Sri Ubaydah Barmawi; Zainal Rafli; Siti Ansoriyah (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
The language used in daily communication is a reflection of a culture that they adheres to, because in communicating, of course, they must have close relationship with the communicant so that the language used can be understood properly and precisely in its meaning. A communication can take place well if the language used can be understood so that the message that the speaker wants to convey to the speech partner is conveyed properly. This study aims to analyze code mixing among participants in the study of the Riyaadush Sholihiin book at the Nurul Iman mosque, Blok M Square, South Jakarta. The method used in this research is descriptive qualitative which does not produce numbers, but in the form of words. The data collection technique used in this research is the listening technique. The results of the study indicate that in communication between the participants, there are 11 code-mixing quotes which are used intentionally so that a religious vibes and conducive atmosphere can be created so that it is expected to motivate participants in the process of learning that religious study.